Numeric–Phenetic Study of Lablab purpureus from East Java Based on Morphology Character and DNA Fingerprinting - Purwanti, Elly; Wangiyana, I Gde Adi Suryawan; Prihanta, Wahyu; Sukri, Akhmad (Universitas Negeri Semarang, 2025)
This research aims to conduct a numeric–phenetic study of Lablab purpureus (L) Sweet based on morphology character and DNA fingerprinting with cophenetic–correlation algorithm confirmation. DNA genome extraction is based on the Blood Animal Plant DNA Preparation Kit. Ten RAPD primers were chosen for the amplification DNA genome, including OPA-6, OPA-8, OPA-10, OPA-20, OPC-19, OPD-8, OPD-12, OPE-8, OPE-15, and OPE-16. Cophenetic correlation is used to analyze three clustering algorithms (Nearest Neighbor, UPGMA, Farthest Neighbor) and five similarity indexes (Simple Matching, Jaccard, Nei & Li, Sorensen, Yule). Lablab purpureus (L) Sweet samples have shown morphology variation, mostly on flowers, pods, and seeds. DNA fingerprinting reveals a variety of band numbers ranging from 300BP to 1000BP. RAPD analysis revealed a total of 87 bands, including 18 polymorphic bands, with an average percentage polymorphism of 31.15%. The UPGMA technique was developed as a result of cophenetic-correlation analysis, and the Jaccard similarity index is the optimal combination for dendrogram generation. The topology of a morphology character dendrogram differs slightly from that of a DNA fingerprinting dendrogram. It concluded that the UPGMA algorithm and Jaccard similarity index is the optimum combination to analyze the diversity of L. purpureus (L) Sweet accession from East Java, resulting in the accession of this species having high diversity. This research can give a novel approaching method in the taxonomy field, which is combining morphological and molecular data.